Hubungan Peran Orangtua dengan Penanganan Awal Diare pada Balita Usia 1-5 Tahun - Lili Suryani; Moza Suzana; Evan Rosiska; Sofhi Dwi Andini (Lembaga Pengembangan Kinerja Dosen, 2026)
According to the latest data from WHO (World Health Organization) in 2024, there were around 1.7 billion cases of diarrhea in children worldwide which resulted in 443,832 deaths in children under 5 years of age each year, and an additional 50,851 children aged 9 years, while the country with the most diarrhea in children in the United States was 350 million cases each year and 48 million of them were caused by bacteria in food. The purpose of this study was to determine the relationship between the role of parents and the initial handling of diarrhea in toddlers aged 1-5 years. This type of research is quantitative analytical with a cross-sectional study approach. The independent variable in the study is the role of parents, while the dependent variable is the initial handling of diarrhea in toddlers aged 1-5 years. The population in this study were all children suffering from diarrhea at the Gedang Village Health Center in 2024 as many as 283 people with a sample of 74 people. The sampling technique used was the Accidental Sampling technique. This study was conducted in the Working Area of ​​the Gedang Village Health Center, Sungai Penuh City, in January-June 2025. The results showed that most 47 (63.5%) respondents had poor parental roles, and most 42 (56.8%) respondents had poor initial handling of diarrhea in toddlers aged 1-5 years, with the results of the statistical test (Chi-Square) obtained a value of p = 0.005 (p <0.05). The conclusion of the study shows that there is a relationship between the role of parents and the initial handling of diarrhea in toddlers aged 1-5 years. The researcher's suggestion from the results of the study is that it can be applied in daily nursing practice, such as providing health education regarding the first handling of diarrhea, so that the role of parents will be even better.